2004
DOI: 10.1063/1.1635993
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear refraction and absorption of Mg doped stoichiometric and congruent LiNbO3

Abstract: Temperature dependence of the absorption and refraction of Mg-doped congruent and stoichiometric LiNbO 3 in the THz rangeThe light induced change of refraction is studied in pure and Mg doped LiNbO 3 with congruent and stoichiometric compositions by the Z-scan method using all-lines visible argonion laser, up to MW/cm 2 intensity level. In Mg-doped congruent and stoichiometric crystals with Mg concentrations above threshold a positive change in the refractive index was found, in contrast to all other cases whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 20 publications
1
29
1
Order By: Relevance
“…5 mol. %, and in periodically poled undoped crystals, the b values are lower by three orders of magnitude at similar experimental conditions (sample thickness and laser power) 12,13,22 that indeed confirms our conclusion on origin of the marked variation of data on b values in as-grown LiNbO 3 crystals at cw-illumination.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…5 mol. %, and in periodically poled undoped crystals, the b values are lower by three orders of magnitude at similar experimental conditions (sample thickness and laser power) 12,13,22 that indeed confirms our conclusion on origin of the marked variation of data on b values in as-grown LiNbO 3 crystals at cw-illumination.…”
Section: Resultssupporting
confidence: 78%
“…20,21 Such an influence is the inherent factor for undoped as-grown crystals. [12][13][14]20 Besides, photorefraction can be controlled (strongly suppressed) by introducing certain dopants (like Mg, Zn, or In), 7,12 or by periodic poling. 13 For example, in the as-grown Mg-doped congruent LiNbO 3 , with a Mg concentration !…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established too, that the value of a quadrupole coupling constant C z of 7 Li nuclei, for all investigated crystals, within an error coincides with well-known value C z = (55.0 ± 0.5) kc [19] at the keeping of axial symmetry of EFG tensor at site of 7 Li nuclei. Dependences of the spectrum central line width (δν 0 ) and quadrupole satellites width (δν 1 ) on the general relative defects quantity of the crystal at θ = 0 • are the most informative results, obtained during 7 Li NMR experiments (θ is the angle between the direction of magnetic field B 0 and axis c of the crystal). Respondent results are illustrated in Fig.…”
Section: Nmr Analysis Of Linbo 3 :Mg Crystalsmentioning
confidence: 99%
“…The analysis of Mg 2+ ions localization in LN structure was made by many researchers and it has been shown that at MgO concentration less than threshold, Mg 2+ ions usually occupy positions of Li + -ions, preventing the appearance of antisite Nb Li ions [5][6][7][8][9]. However, when MgO concentration is above the threshold there are different models of Mg 2+ ions localization in LN crystal: 3.…”
Section: Introductionmentioning
confidence: 99%